The Application of Bicyclo[1.1.1]pentane as a Bioisostere of the Phenyl Ring in Pharmaceutical Chemistry - Fang, Zhuohan; Xu, Qian; Lu, Xuehe; Wan, Nianfeng; Yang, Wu-Lin (Synthesis, 2024)
Bicyclo[1.1.1]pentane (BCP) is a bridging ring skeleton with three-dimensional structure. BCP is a bioisostere of the phenyl ring, tert-butyl group, and alkynes; it has excellent physical and chemical properties compared with phenyl ring, so it has been widely considered by the pharmaceutical chemistry. This short review examines related reports of BCP as a bioisostere of the phenyl ring, and the changes in physicochemical properties and biological activity after substitution. The solubility, clogP, and metabolic toxicity of the drug are improved by BCP bioisosteres, but the biological activity of BCP is lower than the phenyl ring. The application of BCP in drug research and development will be further expanded to provide more possibilities for future drug innovation and development.1 Introduction2 Replacement of Phenyl Rings by BCP3 Conclusion
Keywords: bicyclo[1.1.1]pentane; phenyl ring; bioisosteres; physicochemical properties; pharmaceutical chemistry